2D Dielectrophoresis using an active matrix array made by thin‐film‐transistor technology. Issue 9 (22nd July 2019) - Tixier‐Mita, Agnès; Ihida, Satoshi; Blanchard, Damien; Shinohara, Marie; Eiler, Anne‐Claire; Cathcart, Grant Alexander; Faure, Pierre‐Marie; Kohno, Takashi; Sakai, Yasuyuki; Lévi, Timothée; Toshiyoshi, Hiroshi
Abstract : New types of devices made using thin‐film‐transistor (TFT) technology were used in this article for dielectrophoresis purpose with microbeads, yeast cells, and HepG2 cells. That technology allows obtaining centimeter size transparent substrates covered with a large and dense array of 100 µm microelectrodes individually controllable. The purpose of these devices is the development of platforms for various applications on cells and cells culture, like manipulation, sensing, monitoring, or stimulation on the same device. Dielectrophoresis is one of the applications and is a key target for precise patterning and 2D displacement of cells on the device. In this article, 2D results of dielectrophoresis with microbeads and yeast cells and device programming are described. Then, application to mammal HepG2 liver cells shows the possibility of cells patterning with such devices. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.